Gamification and financial education: A review of pedagogical approaches for teaching in secondary schools - Pacheco Pacheco, Leidy Liset; Flórez Salgado, Karen Angélica (Universidad Francisco de Paula Santander, 2025)
Financial education has gained public importance in recent years as the ideal elements to shape citizens capable of facing economic situations in a globalized world. In this sense, gamification has become one of the new teaching-learning strategies that transforms education by using game dynamics that develop students’ motivation and commitment. From a systematic analysis of the scientific literature from indexed databases, the present study examines the methodologies, effects and problems linked to the implementation of gamification to teach financial education in secondary basic education. The results show that, although gamification can facilitate the reduction of the distance between financial concepts and students, and help to put into practice financial management skills, it is also conditioned by structural elements such as the poor preparation of teachers, the lack of technological resources, or the lack of an adequate curriculum. All in all, we conclude that gamification can be a good proposal for working on processes to promote financial literacy, but it also requires a studied instructional design and rigorous evaluations to ensure the desired educational impact.